El Aula Invertida como estrategia metodológica en el proceso de enseñanza-aprendizaje de la matemática en la Educación Básica Superior - Japón Contento, Carmen Janeth (2024)
This present research work is about the flipped classroom as an innovative methodological strategy the same encourages active participation and student autonomy in the educational process, since it promotes a more dynamic and meaningful learning experience. The stated objective is to determine the contribution of the flipped classroom as a methodological strategy in the teaching and learning process of mathematics in Higher Basic Education. A qualitative descriptive approach with non-experimental documentary design was used, and the data collection technique applied was the filing method to gather the most relevant information for the study. The analysis of the information allowed us to determine a relationship between the characteristics of the variables: flipped classroom and teaching-learning process. The main result obtained based on the documentary analysis indicates that the contribution of the flipped classroom is favorable in the teaching and learning process of mathematics to foster active and autonomous student learning. Keywords: active learning, autonomous learning, flipped classroom as a methodological strategy, teaching-learning process.